A Retrospective Propensity Score‐Matched Early Thromboembolic Event Analysis of Prothrombin Complex Concentrate vs Fresh Frozen Plasma for Warfarin Reversal Prior to Emergency Neurosurgical Procedures. Issue 6 (June 2018) - Agarwal, Prateek; Abdullah, Kalil G; Ramayya, Ashwin G; Nayak, Nikhil R; Lucas, Timothy H
Abstract: BACKGROUND : Reversal of therapeutic anticoagulation prior to emergency neurosurgical procedures is required in the setting of intracranial hemorrhage. Multifactor prothrombin complex concentrate (PCC) promises rapid efficacy but may increase the probability of thrombotic complications compared to fresh frozen plasma (FFP). OBJECTIVE : To compare the rate of thrombotic complications in patients treated with PCC or FFP to reverse therapeutic anticoagulation prior to emergency neurosurgical procedures in the setting of intracranial hemorrhage at a level I trauma center. METHODS : Sixty‐three consecutive patients on warfarin therapy presenting with intracranial hemorrhage who received anticoagulation reversal prior to emergency neurosurgical procedures were retrospectively identified between 2007 and 2016. They were divided into 2 cohorts based on reversal agent, either PCC (n = 28) or FFP (n = 35). The thrombotic complications rates within 72 h of reversal were compared using the χ 2 test. A multivariate propensity score matching analysis was used to limit the threat to interval validity from selection bias arising from differences in demographics, laboratory values, history, and clinical status. RESULTS : Thrombotic complications were uncommon in this neurosurgical population, occurring in 1.59% (1/63) of treated patients. There was no significant difference in the thrombotic complication rate between groups, 3.57% (1/28; PCC group) vs 0% (0/35; FFP group). Propensity score matching analysis validated this finding after controlling for any selection bias. CONCLUSION : In this limited sample, thrombotic complication rates were similar between use of PCC and FFP for anticoagulation reversal in the management of intracranial hemorrhage prior to emergency neurosurgical procedures.